A Study on the Attitudes of Prospective Science Teachers towards the Effects of Mobile Applications and Information Services in Distance Education - Şenay, Volkan; Yılmaz, Malik; Şenay, Burcu Aydemir; Güneş, Ayşenur (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Today, technology is an essential part of human life and use of the technological devices has rapidly increased. Mobile technology products most often used among the technological devices (smart phones, tablets etc.) offer an opportunity for individuals for easily access to all kinds of information they want without a time and place limit. Mobile technology products previously used as a communication device, today, catch the attention of individuals and/ or institutions not only for this purpose, but also making its presence felt in many fields such as trade, education. in the traditional education, also in the distance education, the effect of the information centers and services is important for the information access and sharing of the users to reach to the high level. The presentation of the information resources by the information centers by being digitalized to the users of them is undoubtedly an advantage for the users receiving the distance education. In this study, the description of the opinions of the prospective science teachers concerning the mobile applications and information services in the distance education has been aimed. The sample of the research is composed of Bayburt University and Kastamonu University Primary Science Education Department third class students.